KINERJA KARYAWAN DI ANTARA LINGKUNGAN KERJA DAN KOMUNIKASI SEBUAH PERUSAHAAN JAWATAN - Setiyarti, Tettie; Hariyani, Putu Fajar; Laswitarni, Ni Ketut; Sundari, Pipit (Sekolah Tinggi Ilmu Ekonomi Semarang, 2024)
Every company is expected to be able to manage its human resources well, so that they can be relied on to achieve the company's vision, mission, and targets. The two main factors that influence employee performance in a company are a conducive work environment and the communication style used within the company. This article will focus on discussing and analysing the influence of the work environment and communication on employee performance in a service company, with the Broadcast Program Sector of LPP RRI Denpasar as a case study. The analysis technique that will be used in this article is multiple linear regression analysis. Based on the results of the regression that has been carried out, the regression model used to determine the Employee Performance (Y) is ideal, because the two independent variables, Work Environment (X1) and Communication (X2), both together (simultaneously) and partially, has a positive and significant effect